Techniques and Methods for Developing Special Expertise in Self-Development - Phansri, Natthaporn (Journal of Modern Learning Development, 2025)
Self-development has the ultimate goal of increasing knowledge, expertise, and attitudes appropriate to work performance for the advancement of oneself and the organization. Therefore, self-improvement It is about developing yourself to become a knowledgeable person and have more skills In addition, self-development will be a process to develop one’s own body shape. Developing yourself to speak convincingly and developing oneself to be a creative person People who are always ready to study, acquire knowledge and develop themselves. The theory of development itself is person-centred. Maslow’s Hierarchy of Needs, Murray’s Needs, Boydell’s Self-Development Needs, and Bandura’s Social Learning. Components of self-development include: Self-responsibility. Self-directed learners Providing knowledge through self-direction and social factors The importance of self-development includes knowing oneself in reality, preparing to adjust for the better, and setting guidelines to develop life to reach goals. Self-development includes professional development, development, and mental development. The purpose of self-development is to make individuals aware of the importance of self-development, so that individuals change for the better, to set guidelines for development towards goals, and to provide individuals with an opportunity to review their feelings and needs. Self-development methods include formal education, self-evaluation, personnel development through work experience, and development through relational skills. Specialization means expressing interest, following new knowledge in one’s or related fields of work, having knowledge in academics and technologies in one’s field of work, being able to apply new knowledge, science, or technology to the performance of duties in one’s own organization, continuously studying and developing oneself to have more knowledge and expertise in work, both in depth and breadth, and supporting the work of people in government agencies that emphasize expertise in various fields of science. Knowledge The development of oneself to become a specialist consists of the following components: academic, developmental, and mental self-development guidelines. Self-development methods are obtained from formal education, self-evaluation, and work experience, with the concept and theory supporting self-development, such as the person-centered theory. Maslow’s hierarchy of needs, Murray’s needs theory, Boydell’s self-development theory, and Bandura’s social learning theory come together to form self-development, resulting in specialized knowledge, including academic knowledge, professional expertise, and technological knowledge. In brief, self-development is the development of oneself to become a person with more knowledge and skills. Self-development is the process of developing one’s own physical form, making oneself more eloquent, and developing oneself to become a creative person, ready to study and seek knowledge. Self-development includes professional development, development, and mental development. As for specialized knowledge, it is the interest, knowledge of academics and technology, in which it is applied to the performance of responsibilities, and the continuous development of oneself to have more knowledge and expertise in the work, both in depth and breadth.